Assessment of tissue perfusion of pancreatic cancer as potential imaging biomarker by means of Intravoxel incoherent motion MRI and CT perfusion: correlation with histological microvessel density as ground truth - Mayer, Philipp; Fritz, Franziska; Koell, Marco; Skornitzke, Stephan; Bergmann, Frank; Gaida, Matthias; Hackert, Thilo; Maier-Hein, Klaus H.; Laun, Frederik B.; Kauczor, Hans-Ulrich; Grenacher, Lars; Klauß, Miriam; et al. (Cancer imaging, 2021)
The aim of this study was to compare intravoxel incoherent motion (IVIM) diffusion weighted (DW) MRI and CT perfusion to assess tumor perfusion of pancreatic ductal adenocarcinoma (PDAC).